2016
DOI: 10.1186/s12936-016-1358-7
|View full text |Cite
|
Sign up to set email alerts
|

Low-grade sulfadoxine–pyrimethamine resistance in Plasmodium falciparum parasites from Lubango, Angola

Abstract: BackgroundMalaria is a major parasitic disease, affecting millions of people in endemic areas. Plasmodium falciparum parasites are responsible for the most severe cases and its resistance to anti-malarial drugs is notorious. This is a possible obstacle to the effectiveness of intermittent preventive treatment (IPT) based on sulfadoxine–pyrimethamine (SP) cures administrated to pregnant women (IPTp) during their pregnancy. As this intervention is recommended in Angola since 2006, it has assessed, in this countr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
12
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 44 publications
5
12
1
Order By: Relevance
“…Moderate level of resistance conferred by dhfr and dhps polymorphisms is typically found in West Africa with the absence of I164L polymorphism that is associated with very high-level SP resistance (up to 20 000-fold decrease in susceptibility in comparison with the wild type) [50]. I164L polymorphism have been variously reported in parts of East Africa [51], some parts of South Africa [52] and Asia [53]. There is dearth of information on why I164L mutation does not occur in Africa despite extensive drug pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Moderate level of resistance conferred by dhfr and dhps polymorphisms is typically found in West Africa with the absence of I164L polymorphism that is associated with very high-level SP resistance (up to 20 000-fold decrease in susceptibility in comparison with the wild type) [50]. I164L polymorphism have been variously reported in parts of East Africa [51], some parts of South Africa [52] and Asia [53]. There is dearth of information on why I164L mutation does not occur in Africa despite extensive drug pressure.…”
Section: Discussionmentioning
confidence: 99%
“…25 Pfdhfr and Pfdhps sequences from 20 other countries (18 for Pfdhps and 18 for Pfdhfr) were downloaded from NCBI or our previous study 26 to analyse global genetic diversity. [27][28][29][30][31][32][33][34][35][36]…”
Section: Discussionmentioning
confidence: 99%
“…The codons M74I, N75E, and K76T were the key points for the surveillance of CQR. The SNPs of the pfmdr1 gene were assumed to be associated with the efficacy of multiple antimalarial drugs (20,22). It was reported that the susceptibility of lumefantrine, mefloquine, and dihydroartemisinin could be increasing with the mutation of pfmdr1 86Y, while the resistance of CQ and amodiaquine were increasing (35).…”
Section: Discussionmentioning
confidence: 99%
“…The single nucleotide polymorphisms (SNPs) in pfdhfr and pfdhps were generally shown as multiple mutations. The common SNPs in pfdhfr were A16S, N51I, C59R, S108N, and I164L and in pfdhps were S436A, A437G, K540E, A581G, and A613S (22). Artemisinin resistance to P. falciparum first emerged in Cambodia (23,24), and the polymorphism of the Kelch 13 (K13) propeller domain in P. falciparum was considered a molecular marker of artemisinin resistance in 2014 (25).…”
mentioning
confidence: 99%